2021
DOI: 10.1159/000515085
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Serum Sex Hormone-Binding Globulin, Homocysteine, and Hypersensitive CRP Levels during Pregnancy and Their Relationship with Gestational Diabetes Mellitus

Abstract: <b><i>Background:</i></b> Inflammatory response state is related to the pathogenesis of gestational diabetes mellitus (GDM). <b><i>Objective:</i></b> To investigate the changes of serum sex hormone-binding globulin (SHBG), homocysteine (Hcy), and hypersensitive CRP (hs-CRP) levels during pregnancy and their relationship with GDM. <b><i>Methods:</i></b> The nested case-control study method was used. Sixty nonobese single pregnant women diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Lower SHBG levels in early pregnancy are associated with higher insulin levels, IR, and an increased risk of GDM in mid-pregnancy. Therefore, SHBG can be used to identify high-risk pregnancies in early pregnancy ( 45 , 56 ). Additionally, SHBG expression negatively correlates with GLUT1 and positively correlates with GLUT3 and GLUT4, suggesting SHBG’s involvement in glucose metabolism by regulating multiple GLUTs, binding to sex hormones or other pathways, thereby eliminating IR in GDM ( 57 ).…”
Section: Placental Adipokines and Cytokinesmentioning
confidence: 99%
“…Lower SHBG levels in early pregnancy are associated with higher insulin levels, IR, and an increased risk of GDM in mid-pregnancy. Therefore, SHBG can be used to identify high-risk pregnancies in early pregnancy ( 45 , 56 ). Additionally, SHBG expression negatively correlates with GLUT1 and positively correlates with GLUT3 and GLUT4, suggesting SHBG’s involvement in glucose metabolism by regulating multiple GLUTs, binding to sex hormones or other pathways, thereby eliminating IR in GDM ( 57 ).…”
Section: Placental Adipokines and Cytokinesmentioning
confidence: 99%
“…The innate immune system is the first line of defense against infection. Innate immunity recognizes microorganisms or nonmicrobial antigens, like an allergen or a transplanted organ, and can result in an exaggerated inflammatory response [5][6][7][8][9][10][11][12][13][14][15][16]. Interleukin-6 (IL-6) promotes humoral immunity to protect against extracellular pathogens and stimulates the production of acute-phase reactants such as C-reactive protein (CRP) by the liver [8].…”
Section: Introductionmentioning
confidence: 99%
“…25 Other studies have also linked decreased SHBG levels to higher GDM risk. 26,27 SHBG levels therefore serve as a potential marker to identify women who are at risk for GDM. However, other possible confounding variables, such as prepregnancy body mass index, race/ethnicity and alcohol usage, may influence this connection.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies have shown that lower oestradiol levels are associated with a higher risk of GDM 25 . Other studies have also linked decreased SHBG levels to higher GDM risk 26,27 . SHBG levels therefore serve as a potential marker to identify women who are at risk for GDM.…”
Section: Introductionmentioning
confidence: 99%